Image processing for robot vision application using matlab - Cheong, W.L (Universiti Malaysia Sarawak, UNIMAS, 2010)
Robot vision is one of important sensor used in field of robotics. There are still wide ranges of area to improve the robot vision. The objective of this project is to develop a Graphical User Interface (GUI) application which is user friendly to human and the robot can interpret the segmented object with object recognition. This project will focus on segmentation using edge detection, thresholding and color segmentation. The segmented object will be use in object recognition. The source code is written in MATLAB. The segmentation using edge detection „Sobel Edge Detector‟ and color segmentation using L*a*b* color space are found to be useful in develop the GUI application. Algorithms to segment the required object and to find the object location (distance and centroid coordinates) are found in experiment and proposed into the GUI application. The GUI application is able to work in real-time image effectively in edge detection. Calculation error in the application can be reduced with a good illumination.